2015
DOI: 10.1152/ajplung.00018.2015
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the expression of lung inflammatory mediators in response to ozone

Abstract: Sex differences in the incidence of respiratory diseases have been reported. Women are more susceptible to inflammatory lung disease induced by air pollution and show worse adverse pulmonary health outcomes than men. However, the mechanisms underlying these differences remain unknown. In the present study, we hypothesized that sex differences in the expression of lung inflammatory mediators affect sex-specific immune responses to environmental toxicants. We focused on the effects of ground-level ozone, a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 73 publications
3
95
1
Order By: Relevance
“…The elderly group (65 years and older) showed the highest cardio-respiratory mortality risk with an ER percentage of 1.59 (1.35-1.83) per daily 8-h maximum ozone concentration increasing by 10 µg/m 3 in this study. From a gender perspective, animal experimental research and meta-analysis have shown that women were more susceptible to inflammatory lung disease induced by air pollution and show worse adverse pulmonary health outcomes than men [36,37]. By contrast, our research found a more obvious negative association between ozone exposure and cardiovascular and respiratory mortality among males than females.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…The elderly group (65 years and older) showed the highest cardio-respiratory mortality risk with an ER percentage of 1.59 (1.35-1.83) per daily 8-h maximum ozone concentration increasing by 10 µg/m 3 in this study. From a gender perspective, animal experimental research and meta-analysis have shown that women were more susceptible to inflammatory lung disease induced by air pollution and show worse adverse pulmonary health outcomes than men [36,37]. By contrast, our research found a more obvious negative association between ozone exposure and cardiovascular and respiratory mortality among males than females.…”
Section: Discussioncontrasting
confidence: 67%
“…Because of largely existing pre-conditions or deprived immune systems, elderly people are more vulnerable to ozone exposure than the younger generation [36]. The elderly group (65 years and older) showed the highest cardio-respiratory mortality risk with an ER percentage of 1.59 (1.35-1.83) per daily 8-h maximum ozone concentration increasing by 10 µg/m 3 in this study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…We recovered BAL cells in 2.5 mL of DPBS with 1 mmol/L EDTA and analyzed as described in Cabello et al. (). We determined lipocalin‐2/NGAL levels by ELISA (R&D Systems, Minneapolis MN, kit #MLCN20) in 50 μ L of BAL.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported sex differences in both gene expression and miRNA signatures in response to ozone exposure using mouse models (Cabello et al. ; Fuentes et al. ).…”
Section: Introductionmentioning
confidence: 97%